Shifting-Profits through Tax Loopholes. Evidence from Ecuador - Cyril Chalendard (Center for Economic Studies and ifo Institute (CESifo), 2016)
Based on a natural experiment that took place in Ecuador in the context of a capital outflow tax, this paper presents suggestive evidence of the emergence of an abnormal transfer pricing behavior. We exploit the fact that some imports were eligible to a tax-credit measure aiming to offset the capital outflow tax. The identification strategy relies on the fact that a foreign multinational enterprise has only an incentive to increase the unit value -transfer price- for profit shifting motivations of products eligible to the tax-credit. Then, comparing the evolution of the unit value of eligible products (the treatment group) with that of non eligible products (the comparison group) before and after the tax-credit measure, we estimate the over-reporting incentive's impact on the reported value. Results show that the declared unit value of eligible imports increased following the introduction of the tax-credit measure. Various tests suggest that this abnormal increase is attributable to a profit-shifting behavior.
Keywords: F13; H25; H26; H32; K42; 330; profit-shifting; tax evasion; transfer pricing; tax loophole; capital outflow tax; customs reform